2022
DOI: 10.3389/fimmu.2022.938837
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of potential common pathogenic mechanisms for COVID-19 infection and primary Sjogren’s syndrome

Abstract: BackgroundAccumulating evidence has revealed that the prevalence of Coronavirus 2019 (COVID-19) was significantly higher in patients with primary Sjogren’s syndrome (pSS) compared to the general population. However, the mechanism remains incompletely elucidated. This study aimed to further investigate the molecular mechanisms underlying the development of this complication.MethodsThe gene expression profiles of COVID-19 (GSE157103) and pSS (GSE40611) were downloaded from the Gene Expression Omnibus (GEO) datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…Moreover, we unveiled a tight co-expression relationship among these hub genes for the first time. Other studies have revealed shared hub genes between COVID-19 and primary Sjogren's syndrome (Luo and Zhou 2022 ) or rheumatoid arthritis (Hu et al 2022 ), such as MX1 and RSAD2, consistent with this study, indicating that the identified hub genes and their co-expression relations might be promising biomarkers for pan-ADs and COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we unveiled a tight co-expression relationship among these hub genes for the first time. Other studies have revealed shared hub genes between COVID-19 and primary Sjogren's syndrome (Luo and Zhou 2022 ) or rheumatoid arthritis (Hu et al 2022 ), such as MX1 and RSAD2, consistent with this study, indicating that the identified hub genes and their co-expression relations might be promising biomarkers for pan-ADs and COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…Contemporary, the rapid advances in bioinformatics approaches allow us to delve deeper into the molecularlevel investigation of disease-disease interactions and co-pathogenesis [23][24][25][26]. To discover the biological mechanisms of LUAD and PAH, we used the weighted gene co-expression network analysis (WGCNA) to discover the co-expression cluster and connected shared genes in these two diseases and explored potential drug molecules using molecular docking.…”
Section: Introductionmentioning
confidence: 99%
“…Sjogren’s syndrome (SS) is a systemic autoimmune chronic disease characterized by marked exocrine glandular dysfunction such as salivary and lachrymal glands, presenting a persistent dryness of mouth and eyes 1 . In some areas like China, the prevalence can reach as high as 5.6%, with a female-to-male ratio of 9:1 due to an association with hormonal changes 2 . SS process can also extend to several other organs and tissues including lungs, kidneys, blood vessels, skin, and nervous system, which may impair patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%